Ubezpieczenia zdrowotne - szanse, zagrożenia oraz perspektywy ich rozwoju w polskich realiach - Gubernat, Ewa (Health Insurance - Chances, Threats and Prospects of its Development in Poland, 2006)
Health is one of the most important values in human life. As the general system of health insurance is unolergoing financial slump and because health insurance fees are insufficient, one has to search for other alternative ways of insurance. And so voluntary health inurance is considered more frequently. It is possible to distinguish a lot of chances for the development of this market. However, as society is not educated enough this is the biggest barrier to popularize health insurance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 109-116